Síntese de pseudodissacarídeos de interesse em leishmaniose via cicloadição 1,3-dipolar - Luiza dos Reis Cruz (2014)
Leishmaniasis are parasitic neglected tropical diseases caused by protozoa of the genus Leishmania and is transmitted to humans by female vectors of the genus Lutzomyia. The life cycle begins with the transmission of protozoa to man in the form of metacyclic promastigotes, during blood feeding of female sand flies infected with parasites. These promastigotes are then phagocytized by cells of the mononuclear phagocyte system. The adhesion which starts the process of phagocytosis involves the recognition of molecules exposed on the surface of the parasite, such as lipophosphogycan and glycoprotein gp63. These molecules bind to different receptors on the surface of macrophages of the host, such as mannose receptors. It has been shown that mannose receptor ligands are able to partially block the adhesion of L. donovani promastigotes into human macrophages. It is possible that ribose derivatives connected to a D-mannose unit can form complexes with antimony which could be internalized into macrophages via the mannose receptor. Thus, the aim of this work is the synthesis of pseudo disaccharides linked by a triazol ring for the complexation with antimony and subsequent pharmacological evaluation. For the convergent synthesis of pseudo disaccharides, 1,3-dipolar cycloaddition was used. As dipolarophiles, propargyl glycosides derived from D-glucose, D-galactose and D-mannose were obtained with 54%, 80% and 34% yield, respectively. As 1,3-dipoles, organic azides derived from D-ribose and 5-methyluridine, were obtained with 94% and 57% yield, respectively. The protected pseudo disaccharides were obtained by the 1,3-dipolar cycloaddition catalyzed by copper with a yield between 41% and 75%. The deacetylated pseudo disaccharides were obtained by the method of Zemplen with a yield between 64% and 87%. Preliminary studies on the synthesis of antimony complexes were initiated. The deacetylated pseudodissacarídeos are being evaluated for pharmacological activity.